A Study On Application Of Blockchain Technology To Control Counterfeit Drugs, Enhance Data Privacy and Improve Distribution In Online Pharmacy - Deepnshu Singh; Jyotinder Kaur Chaddah (ACHSM, 2021)
Technology has always emerged to embolden the existing working process. On the one hand, it encourages transparency, accessibility and robustness in the system and on the other hand, it begets mitigation of the risks and allows us to detect, evaluate and eliminate vulnerability in the system. The most prominent technologies in todays' world like Artificial Intelligence, Virtual/Augmented Reality, Automation, Cloud Computing are thriving to solve society's problems and ensure the expedition in the process from its previous generation. Blockchain technology is no exception in providing the solution to eliminate the counterfeit markets across the globe and building trust among parties to do business without the fear of indulging or facing any unscrupulous business. Blockchain technology can ensure data privacy while improving supply chain transparency and reducing fraud. It can provide all stakeholders within a certain supply chain with access to the same information, potentially reducing errors. A decentralised application can pave the way to promulgate online pharmaceutical business where health information and each stakeholders' data is not compromised. Against this backdrop the research conducted throws light on the challenges in the online medical drug and devices' distribution and proposes a solution, an architectural design for blockchain technology in an online pharmaceutical platform to mitigate the counterfeit market while bringing efficiency to the ecosystem.